The influence of service quality dimensions on customer satisfaction within visa facilitation services centres in Gauteng - Matthews, Modiri (Vaal University of Technology, 2022)
The provision of government services in an orderly, efficient and caring manner has been a matter of huge concern within the public domain and largely a contentious topical area within media and other institutions that observe such functions. In the case of foreign nationals who wish to reside in South Africa, the relevant documentation is a visa that allows such persons to visit, study, work or run a business in South Africa, amongst others The primary objective of this study was to investigate the influence of service quality dimensions towards customer satisfaction within visa facilitation services in Gauteng. The study focused on foreign national students from a selected higher education institution (HEI) who require visas to study in South Africa. The five service quality dimensions that were considered as predictors were reliability, assurance, empathy, responsiveness and tangibility. In addition, the expectant disconfirmation theory (EDT) was considered critical in this study. In order to achieve the primary objective of the study, a quantitative cross-sectional research approach was employed and a non-probability convenience sampling procedure was adopted. A pilot study preceded the main survey to confirm the reliability of the measurement scale. Thereafter, a structured questionnaire was utilised to survey two hundred and ninety-seven students from the selected HEI and the resultant response rate was 100%. Coded data was transformed and descriptive statistics (profile data frequency table, means and standard deviation) exploratory factor analysis, and correlations were done using Statistical Package for the Social Sciences (SPSS) version 26.0. Finally, LISREL software for statistical analyses was employed to perform structural equation modelling procedure using the various indices to determine the model fit for both the measurement and the structural models. The determination of the structural model fit was followed with a summary of the five hypothesised relationships. Specifically, only two hypotheses (H1-reliability and H4-empathy) stated were supported in a significant way, while the other two hypotheses (H3-tangibility and H3- responsiveness) were positive; however, they were insignificant and thus not supported. Furthermore, the remaining hypothesis (H2-assurance) was negative and insignificant and therefore not supported. The study proposes both the theoretical and practical contributions in the form of recommendations and also provides support for further research endeavours in the area. In addition, the outcome of this study provides a useful tool for gaining insight into service quality dimensions considered as important by foreign nationals requiring visas. The study concludes by alluding to the limitations and implications for further research.
M. Tech. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Expectant disconfirmation theory; Service quality dimensions; Customer satisfaction; Visa facilitation services and foreign nationals; Dissertations, Academic -- South Africa.; Customer satisfaction.; Visas -- South Africa.; Student passports.